Jane Goodall, protector of chimpanzees - Meachum, Virginia (Springfield, NJ, USA : Enslow Publishers, 1997)
Explores the life and research of the English animal behaviorist who undertook the first long-term study of chimpanzees in the wild.
Includes bibliographical references (p. 101) and index.
Keywords: Goodall, Jane, -- 1934- -- Juvenile literature; Goodall, Jane, -- 1934-; Primatologists -- England -- Biography -- Juvenile literature; Chimpanzees -- Tanzania -- Gombe Stream National Park -- Juvenile literature; Chimpanzees; Zoologists; Women -- Biography